AN ANALYSIS OF SLANG WORD IN THE LYRICS OF AVRIL LAVIGNE'S SONG IN THE ALBUM "HEAD ABOVE WATER" BY CLASS XI IPA 2 SMAN 2 KUTACANE IN ACADEMIC YEAR 2023/2024 - Dinda Andraini; Raja Fauziah; Edi Syahputra (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
A Thesis English Education Department High School of Teachers Training and Education, stkip us Kutacane. The aim of the research was to identified the types of slang words contained in Avril Lavigne's song lyrics in the album "Head Above Water" by Class XI IPA 2, to find out the meaning of slang words in Avril Lavigne's song lyrics in the album "Head Above Water" by Class XI IPA 2, to analyze slang words found in Avril Lavigne's song lyrics in the album " Head Above Water" by Class XI IPA 2. The research data was taken from the lyrics of Avril Lavigne's song on the album "Head Above Water". The data is analyzed by identifying songs inti four types of processes, classifying words in each type of slang, anlyzing the data into slang words. It was found that there are three types of slang in the lyrics of Avril Lavigne's song on the album "Head Above Water" by Class XI students of Science 2 namely blending ( 41,05% ), coinage ( 44,75% ), clipping ( 56,85% ) and also found its meaning, namely: conceptual, connotative, affective, reflective, collocative and thematic. The author found the most common type of slang is blending between slang words in 8 selected song lyrics Avril Lavigne's on the album "Head Above Water" by Class XI students of Science 2. The author realized that these words were slang words found in the lyrics of Avril Lavigne's song on the album "Head Above Water" by reading all the lyrics in detail and analyzing the word by trying to find the right word or its true meaning. Then the researcher can decided the word is referred to as a slang word.